Prenatal detection and molecular cytogenetic characterization of Xp deletion and Xq duplication: a case report and literature review - Qing Lin; Chunya Liang; Bole Du; Lijiao Li; Hong Li; Xiaolan Mai; Sheng Li; Wenyu Xu; Cunzhen Wu; Mi Zeng (BMC, 2024)
Abstract Background Copy number variation (CNV) of X chromosome can lead to a variety of neonatal abnormalities, especially for male fetuses. In recent years, due to the high sensitivity and high specificity of NIPS, its application has gradually expanded from chromosome aneuploidy to CNV. Few prenatal cases involving the detection of Xq duplication and deletion by NIPS have been reported, but it is of great significance for genetic counseling. Case presentation A 36-year-old woman was referred for prenatal diagnosis and genetic counseling at 17 weeks of gestation because of abnormal result of noninvasive prenatal screening (NIPS). Multiple congenital malformations, hydrocephalus, and enlarged gallbladder were observed by prenatal ultrasound. Amniocentesis revealed the karyotype of the fetus as 46, XN, add(X) (p22.2) and the result of chromosomal microarray analysis was arr[hg19] Xq27.1q28(138,506,454-154896094) × 2 and arr[hg19] Xp22.33p22.32(168,551-5,616,964) × 1. CNV-seq showed that the mother shares a 16.42 Mb duplication in the Xq27.1-q28 region and a 2.97 Mb deletion in the Xp22.33-p22.32 region. After genetic counseling, the couple chose to terminate the pregnancy. Conclusion The combination of NIPS and CMA would be of values in detection of subchromosomal duplications and/or deletions at fetal stage. The detection of X chromosome aberration in a male fetus should give suspicion of the possibility of maternal inheritance.